Influence of static strength on the fatigue resistance of welds - Steimbreger, Ceferino (2018)
The present paper deals with a fracture mechanic approach that employs the Resistance-Curve concept, in order to predict fatigue endurances of welded components, with different tensile strengths of the base metal. The Resistance-Curve method compares the total driving force applied to a crack with its threshold for propagation, both defined as a function of crack length. The former depends on load scheme and weld geometry and it can be obtained from finite element analyses, while the second is inherently related to weld resistance. Results obtained herein showed that threshold curve shape is changed when static strength of the base material is modified. Consequently, its interaction with the driving force differed, giving raise to different fatigue endurances for various values of the tensile strength. However, this effect is only likely to be leveraged, provided that the initial crack length is small enough. In real welded structures, the presence of defects demands longer initial crack lengths to be used in calculations, at which the benefit of enhanced strength is minimised or even inverted. Moreover, at these lengths, the growing process is mainly controlled by weld geometry and long crack propagation threshold, whereas local properties become less important in fatigue limit prediction.